Analisis Kinerja Karyawan Ditinjau dari Aspek Motivasi dan Lingkungan Kerja pada PT Gunung Sindur Kabupaten Bogor - Raden Yeti Sumiaty; Esti Suntari; Sam Cay (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This study was conducted in response to the increasing importance of employee performance in achieving organizational effectiveness, particularly in relation to motivation and the work environment. Many organizations recognize that employee performance is not solely determined by individual capability, but also by psychological and environmental factors that shape work attitudes and productivity. This research employed a descriptive quantitative method and was carried out at PT Gunung Sindur. The research subjects were all employees of the company, with annual employee performance appraisal reports serving as the primary data source. These reports contained information on motivation, work environment, performance, and work productivity. To strengthen the findings, semi-structured interviews were conducted with the HR Manager, supervisors, and five employees with the longest tenure. The data were analyzed using descriptive statistical techniques. The findings indicate that employee motivation and the condition of the physical work environment significantly influence performance. Many employees expressed dissatisfaction with the reward system, perceived salary inequity relative to responsibilities, and reported limited involvement in decision-making. Additionally, uncomfortable room temperatures, high noise levels, and limited workspace reduced overall comfort. These results highlight the importance of enhancing motivation and improving the work environment to optimize employee performance.